Implicit innovation of a small school on the socio-educational margins. The school In and Beyond - De Vitis, Francesca (Formazione & insegnamento, 2019)
Reading the Manifesto of Small Schools, and the latest research, there is an implicit invitation to a reflection, not new, but constant, which concerns the historical mandate of educational responsibility that the company recognizes for the school. Mandate to which the Small and Big Schools must respond. Own Educational Responsibility also for those schools that, even if they belong to the group of large schools, practice learning in completely different spaces and places, and that much, seem to have in common with the Small Schools. The Little School of which we are speaking, is the one that carries out its mandate within the prison. A school whose mission does not end in the “In” but must look “Beyond”.